The effectiveness of emotion-focused cognitive therapy on corona anxiety, sense of coherence and post-traumatic growth in women recovered from corona - Zadhasan, Zohreh; Gholamzadeh Jofreh, Maryam (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This study was conducted with the aim of determining the effectiveness of emotion-oriented cognitive therapy on anxiety of Corona, sense of coherence and post-traumatic growth in women recovered from Corona. Methods: The research method was quasi-experimental with a pre-test-post-test design and follow-up with a control group. The statistical population of the research was all women who recovered from Corona in the city of Babol in 2021. The sample size of the study included 30 women who recovered from Corona, who were selected by the available sampling method and according to the study entry and exit criteria. The experimental group received the emotion-oriented cognitive therapy intervention based on the protocol provided by Power (2010) in 10 weekly 90-minute sessions. The questionnaires used in this research include the growth questionnaire. After Tedeschi and Calhoun’s accident (1996), Corona Anxiety Questionnaire by Alipour et al. (2019) and Antonovsky’s Coherence Questionnaire (1993) The data were analyzed by variance analysis with repeated measurements in spss.22 software. Results: The findings showed that in the post-test between the test groups and evidence in terms of corona anxiety (F=12.86, P<0.001), sense of coherence (F=60.34, P<0.001), and post-traumatic growth (F=79.61, P<0.001) There was a significant difference. In other words, the intervention of emotion-oriented cognitive therapy improved the level of anxiety of Corona, sense of coherence and post-traumatic growth of women recovered from Corona. Conclusion: According to the findings of the present study, it is possible to suggest emotion-oriented cognitive therapy intervention as an effective method to increase corona anxiety, sense of coherence and post-traumatic growth of women recovered from corona.